Portuguese colonial cities: local dynamics, global flows (c.1500-1900) - Mota, Maria Sarita; Atallah, C. C. A.; Dominguez, R. (2022)
Considering that every empire is a global system, the concept of “imperial cities” and “colonial cities” has been useful in the study of the territorialization and urbanization of European overseas empires. For a long time, it allowed researchers to focus on a broader urban system, incorporating all the spaces produced by urbanization understood as a social process. However, more than comparing early modern cities, it is necessary to show how the historical trajectory of some settlements is reflected in their organization as urban networks. Facing this challenge, the chapters of this book reveal that political categories of Portuguese urbanism such as townships, villages, and cities, which in some cases were connected to imperial and trans-imperial spaces, hide much more complex dynamics. Understanding these spaces as “entangled cities”, the authors seek to answer a question that has been asked by some urban scholars: would colonial cities also be global cities?